(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The article suggests the use of intermediary agencies for development of joint activities between state-owned enterprises and enterprises with partners who have sufficient financial resources for the development of new wells and the conclusion is preserved in a cost-effective power production of energy and other stakeholders in joint activities of organizations (UNIVERSITIES and research institutes, leasing companies, insurance companies, consulting companies, banking institutions and other financial institutions, suppliers of equipment for gas plants, the chamber of Commerce) and highlighted important socio-economic effects of a joint activity for each participant of this project to reduce economic risk, the main types of articles and management costs. The authors found that each of the objects of the joint activity should take specific local specific mechanisms, based on the specifics of wells and the status of its owner, and developed the triangle to attract intermediaries to optimize risk and management costs with the release of positive effects from participation in such activities for each of the participants, territorial and/or regional socio-economic problems